2023
DOI: 10.3389/fsurg.2023.1130566
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative free flap monitoring in reconstructive surgery—man or machine?

Abstract: Free tissue transfer is widely used for the reconstruction of complex tissue defects. The survival of free flaps depends on the patency and integrity of the microvascular anastomosis. Accordingly, the early detection of vascular comprise and prompt intervention are indispensable to increase flap survival rates. Such monitoring strategies are commonly integrated into the perioperative algorithm, with clinical examination still being considered the gold standard for routine free flap monitoring. Despite its wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 109 publications
0
24
0
Order By: Relevance
“…There were only seven sentinel events, with the majority being related to hematoma formation. that in a darker complected patient population, clinical examination alone also has potential for monitoring issues and thus implementing objective data should be a focus for further investigation and may be impetus to perform dual monitoring in this patient population (Knoedler et al, 2023). In our study population only three of the 48 patients studied were Black or dark-skinned and none of these patients developed complications.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…There were only seven sentinel events, with the majority being related to hematoma formation. that in a darker complected patient population, clinical examination alone also has potential for monitoring issues and thus implementing objective data should be a focus for further investigation and may be impetus to perform dual monitoring in this patient population (Knoedler et al, 2023). In our study population only three of the 48 patients studied were Black or dark-skinned and none of these patients developed complications.…”
Section: Discussionmentioning
confidence: 90%
“…Older data demonstrated that NIRS technology had been shown to have reduced efficacy in darker skinned patients, however, in a recent session of the American Association for Hand Surgery, data were presented evaluating the use of NIRS for detecting induced digital ischemia in light and dark‐skinned patients and found that NIRS was accurate in predicting digital ischemia in both clinical scenarios (Isaac Fleming et al, n.d.; Wassenaar & Van den Brand, 2005). Prior work has demonstrated that in a darker complected patient population, clinical examination alone also has potential for monitoring issues and thus implementing objective data should be a focus for further investigation and may be impetus to perform dual monitoring in this patient population (Knoedler et al, 2023). In our study population only three of the 48 patients studied were Black or dark‐skinned and none of these patients developed complications.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, postoperative flap monitoring was performed through clinical examination and Doppler ultrasound. Further technical innovations such as dynamic infrared thermography, hyperspectral imaging, or laser speckle contrast analysis have been proposed to support and refine flap monitoring in recent years [41]. Although clinical examination in combination with acoustic Doppler sonography is still considered the gold standard, novel technologies can objectify the assessment and support the examiner in decision making.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the specific light source used to inspect the FFF and dark skin tone represent additional pitfalls when evaluating FFF failure ( 137 , 139 , 140 ). Monitoring of buried FFFs is even more challenging as there is no direct access postoperatively to the bony segment and the use of ADS is commonly limited to superficial vessels ( 141 ). To overcome such obstacles novel strategies in postoperative free flap monitoring were developed, namely (i) color duplex ultrasonography (CDS), (ii) flow coupler (FC), (iii) implantable doppler (ID), (iv) laser doppler flowmetry (LDF), (v) near-infrared spectroscopy (NIRS), and (vi) hyperspectral imaging (HSI).…”
Section: Progress In the Postoperative Period – The Advent Of Modern ...mentioning
confidence: 99%